Tribological analysis of diamond-like carbon coatings in combination with bio-lubricants for engine cam tappet interaction / Rehan Zahid - Rehan , Zahid (2017)
In an internal combustion engine, a considerable improvement in tribological performance of components operating under boundary lubrication regime, like cam-tappet interface of valve train assembly, can be achieved by depositing diamond-like carbon (DLC) coatings. These coatings possess a unique combination of properties with the help of which they can help in minimizing friction induced energy and material losses. The lubricity of DLC coatings can be further enhanced by using lubricants having polar components and an unsaturated structure such as vegetable oils. Fossil fuel reserves are depleting at a rapid pace and there are many environmental/health issues associated with conventional lubricants. Therefore, there is a need to shift to environmentally sustainable and biodegradable ones. Bio-based lubricants especially chemically modified vegetable oils such as trimethylolpropane ester of palm oil (TMP) have certain characteristics which make them potential candidate for substituting conventional base oils. Since, lubricant additives are manufactured to interact synergistically with conventional base oils and metallic surfaces, therefore, the main focus of the research presented in this thesis is to analyze tribological compatibility of TMP with most widely used lubricant additives [Glycerol Mono-Oleate (GMO), Molybdenum Dithiocarbamate (MoDTC), Zinc Dialkyldithiophosphate (ZDDP)] in combination with various types of DLC coatings [hydrogen-free tetrahedral DLC coating (ta-C), hydrogenated amorphous DLC coating (a-C:H) and tungsten-doped DLC coating (a-C:H:W)]. Three formulated versions of TMP were prepared by mixing 1 wt.% of GMO, MoDTC and ZDDP separately in 99 wt.% of base oil whereas fourth sample was synthesized by mixing 1 wt.% of each additive in 97 wt.% of base oil. For reference, PAO was used as conventional base oil, with and without additives. Extreme pressure characteristics of lubricant samples on steel/steel contact were evaluated using four-ball wear tester whereas tribological performance of steel/steel, DLC/steel and DLC/DLC contacts had been evaluated using a universal wear testing machine. Moreover, cylinder head tests were also performed using a direct acting valve train test rig and valve train performance parameters of a DLC-coated cam/tappet interface were compared with those of uncoated ones. Mechanisms responsible for a particular tribological behavior were investigated using various material characterization techniques. Formulated and additive-free versions of TMP showed superior extreme pressure characteristics and resulted in higher weld load values compared to PAO-based lubricants due to their polar structure and better lubricity. During the tribotesting phase, up to 73% and 97% reduction in friction and wear coefficient values were observed respectively when DLC-coated surfaces were used instead of uncoated ones. Symmetrical a-C:H contact proved to be tribologically most efficient among all the considered contacts. In single additive-containing lubricants, TMP+GMO facilitated the sliding between uncoated and DLC-coated surfaces whereas TMP+ZDDP resulted in maximum surface protection. When multi-additive containing lubricants were used, PAO+GMO+MoDTC+ZDDP demonstrated lowest friction coefficient values whereas TMP+GMO+MoDTC+ZDDP was proved to be most effective in mitigating the wear of contact surfaces. During cylinder head testing, significant improvement in wear resistance of valve train components was observed when a-C:H-coated tappets were used against a-C:H-coated camlobes in the presence of TMP+GMO+MoDTC+ZDDP.